On a conjecture of Gill on Bell experiments - Rubin, Daniel B. (Examples and counterexamples, 2025)
This note gives a counterexample to a conjecture of Richard Gill that was stated as open problem related to the statistical analysis of Bell experiments in quantum mechanics, and which can formulated as an elementary probability problem.